2004
DOI: 10.1037/1040-3590.16.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Are Dietary Restraint Scales Valid Measures of Acute Dietary Restriction? Unobtrusive Observational Data Suggest Not.

Abstract: The finding that dietary restraint scales predict onset of bulimic pathology has been interpreted as suggesting that dieting causes this eating disturbance, despite the dearth of evidence that these scales are valid measures of dietary restriction. The authors conducted 4 studies that tested whether dietary restraint scales were inversely correlated with unobtrusively measured caloric intake. These studies, which varied in foods consumed, settings, and populations, indicated that common dietary restraint scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
282
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(298 citation statements)
references
References 63 publications
12
282
3
1
Order By: Relevance
“…This pattern of findings is informative for one important measurement issue. Cross-sectional studies (e.g., Stice et al, 2004) have reported that measures of dietary restraint do not measure actual caloric restriction. The results of this study indicate that these four measures of dietary restraint were not predictive of changes in energy balance and that they were not informative of a current state of negative energy balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of findings is informative for one important measurement issue. Cross-sectional studies (e.g., Stice et al, 2004) have reported that measures of dietary restraint do not measure actual caloric restriction. The results of this study indicate that these four measures of dietary restraint were not predictive of changes in energy balance and that they were not informative of a current state of negative energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, a few studies have failed to support the hypothesized causal relationship between dietary restraint and overeating/binge eating (Dritschel, Cooper, & Charnock, 1993;Jansen, Oosterlaan, Mercklbach, & van den Hout, 1988;Lowe & Kleifield, 1986;Smith, Geiselman, Williamson et al, 1998;Wardle & Beales, 1987). Several authors (e.g., Lowe & Levine, 2005;Ouwens, van Strien;& van der Staak, 2003;Stice, Fisher, & Lowe, 2004) have concluded that the mixed results of different studies are most likely due to different methods being used for measuring dietary restraint, i.e., the Restraint Scale versus several alternatives that are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between dietary restraint, food intake and body weight vary across populations Some researchers have questioned the validity of the restraint construct on the basis that dietary restraint scores do not show reliable associations with food intake [27][28][29] or energy balance. 30,31 However, others have challenged this, arguing that restraint scales do not attempt to measure food intake, but rather a cognitively mediated attempt to eat less than desired.…”
Section: Widely Used Methods Of Measuring Dietary Restraint Confound mentioning
confidence: 99%
“…One explanation for the contradictory findings is that dietary restraint scales may not be valid measures of dietary restriction. Multiple studies (Jansen, 1996;Stice, Fisher, & Lowe, 2004;van Strien, Cleven, & Schippers, 2000), varying in food types consumed, settings examined, and populations studied, found that dietary restraint scales were not inversely correlated with objective measures of acute caloric intake, in contrast to the original validity studies that found these scales correlated negatively with self-reported intake (Laessle, Tuschle, Kotthaus, & Pirke, 1989;van Strien, Frijters, van Staveren, Defares, & Deurenberg, 1986). Similarly, Bathalon and associates (2000) found that one restraint scale did not correlate with an objective biological measure of longer-term caloric intake (over an 18-day period).…”
mentioning
confidence: 99%